Some Thoughts About Planning Coastal Shelterbelts - Singh, S. P. (Indian Forester, 1982)
India has a long history of cyclonic and flood damage. Occurrence of severe cyclones is be coming more frequent. It is known that these recurrent problems should be dealt at their root and not by merely treating after-effects and consequences why then there is failure of Govt. In planning to meet periodically recurrent devastating cyclonic force. Tbe paper analyses this situation and brings out the need for giving due weightage to social environment in project formulation.